Study of the content of certain heavy metals in the soft tissue of the (Viviparus viviparus L.) that inhabitates the river of Sozh in Gomel - Makarenko Тatiana V.; Hryshchanka, Ilya V.; Makarenko, Andrei I.; Nikitin, Alexander N. (Journal of the Belarusian State University. Ecology, 2021)
The soft tissues of molluscs are the components that make it possible to establish the degree of influence of the urban agglomeration on the pollution of the components of the aquatic ecosystem, which do not have a visible anthropogenic load, with compounds of heavy metals. The content of the heavy metals under investigations (except for nickel) decreased in comparison with the data obtained in 2002, which indicates a decrease in anthropogenic load on the aquatic ecosystems of the Sozh. The high content of copper, cobalt and nickel before the city’s wastewater is received confirms the influx of pollutants with the surface runoff of agro-residential areas and settlements located upstream of the city along the river. Unidirectional decrease in copper concentration downstream of the Sozh testifies to the course of ecosystem self-cleaning processes. Confirmation of these processes is a significant decrease in the content of lead and chromium in the area outside the city, in comparison with the section of the river within the city limits. The abnormally high concentration of lead and chromium in the soft tissues of Viviparus viviparus L. in the river section within the city limits, nickel and cobalt below the city limits, indicates the flow of metals into the river with the surface runoff of the city. The high level of metal content in the old complex shows the need to conduct a study on the content of pollutants in aquatic ecosystems that do not have a visible anthropogenic load, but are used by the population for recreational purposes.